Implementasi Disiplin Aparatur Sipil Negara Menurut Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin Pegawai Negeri Sipil - Marhendi, Marhendi; Garmayu, Perliana (FOCUS: Jurnal of Law, 2021)
The position of Civil Servants (PNS) is vital and determines the success of the government's mission. One of the factors considered important is creating a clean and authoritative state apparatus, namely the discipline of civil servants. To discipline Civil Servants, the government issued Government Regulation No. 53/2010 concerning Civil Servant Discipline. The purpose of this study was to determine and study: (1) the implementation of the Discipline of the State Civil Apparatus at the Cakrabhuwana Airport Office in Cirebon, and (2) the inhibiting factors for the implementation of the Discipline of the State Civil Apparatus at the Cakrabhuwana Airport Office in Cirebon. This research approach is a combination of normative legal research with empirical legal research,.Namely, this research examines data based on existing norms regarding the implementation of Government Regulation Number 53 of 2010 concerning Civil Servant Discipline. All data obtained from the research results were analyzed qualitatively, then presented descriptively based on the existing problem formulations, and finally, a conclusion was drawn. The results showed that: (1) in implementing the work discipline enforcement of employees at the Cirebon Cakrabhuwana Airport Office refers to Government Regulation Number 53 of 2010 concerning Civil Servant Work Discipline. When there are civil servants who violate disciplinary rules, they will be subject to disciplinary sanctions or penalties according to the type of violation committed. The imposition of sanctions or disciplinary penalties for civil servants who violate discipline is carried out by direct superiors as long as they are under their authority, and (2) factors that affect the implementation of discipline enforcement of Civil Servants at the Cirebon Cakrabhuwana Airport Office are divided into 2 (two). First, the supporting factors are the factors of rules (law), facilities and infrastructure, and respect for Civil Servants. Second, the inhibiting factor is the self-awareness of Civil Servants and the budget factor.